THE RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDES OF PREGNANT WOMEN WITH COMPLIANCE WITH IRON TABLET CONSUMPTION (FE) AT THE BANDA SAKTI HEALTH CENTER, LHOKSEUMAWE CITY YEAR 2023 - Izzah, Intan Nur; Yuziani, Yuziani; Albin, Iskandar (E-Jurnal Medika Udayana; Vol 13 No 5 (2024): E-Jurnal Medika Udayana, 2024)
Anemia is a condition of low levels of red blood cells, hemoglobin capacity, and hematocrit volume in each milliliter of blood when it is sufficient to meet the body's physiological needs. If a person has hemoglobin levels below 12 g/100 ml in their blood, it can be said that the person has anemia. Anemia is one of the health problems experienced by many pregnant women. One way to prevent anemia in pregnant women is to consume iron (Fe) tablets. However, the compliance of pregnant women in consuming iron tablets is still low, this is caused by various factors such as attitudes and knowledge which will later influence the formation of health behavior. This research aims to determine the relationship between knowledge and attitudes of pregnant women and compliance with consuming iron (Fe) tablets at the Banda Sakti Health Center in 2023. This research is an observational analytic research with a cross sectional approach with sampling using the accidental sampling method with 100 respondents. Data analysis used in the research includes univariate analysis and bivariate analysis using the chi-square test. The research results showed that the majority of respondents had insufficient knowledge, namely 44%, and the majority of respondents had a very negative attitude, namely 39%, and the majority of respondents, namely 56% of respondents, were disobedient. Proven by the chi-square statistical test which shows the relationship between knowledge and adherence to consuming iron (Fe) tablets. So the researchers concluded that there was a significant relationship between knowledge and compliance of pregnant women in consuming iron tablets. Keywords: Anemia, ANC, folic acid